MUSIK PUNK SEBAGAI EKSPRESI KEWARGANEGARAAN KRITIS: ANALISIS WACANA KRITIS KRITIK TERHADAP APARAT NEGARA DALAM LIRIK LAGU 'BALADA GEHEL' KARYA DONGKER - Yayang Ramadhan; Sapriya; Vini Agustiani Hadian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the representation of state authorities in the song lyrics of Balada Gehel by Dongker and examine its function as a form of critical citizenship expression. The research employs a qualitative approach using Critical Discourse Analysis (CDA) by integrating the frameworks of Teun A. van Dijk and Norman Fairclough. The data consist of song lyrics, audiovisual documentation, and contextual sources related to Indonesia’s socio-political conditions in 2020. The findings reveal that state authorities are represented through degradative metaphors, institutional delegitimization, and emotional contrasts that reflect criticism of power practices. Furthermore, the song functions as a medium of civic expression that expands democratic participation through popular culture. The study suggests that punk music has significant potential as a contextual learning resource for fostering civic sensibility and civic responsibility within Citizenship Education.